(untitled) (E Conference Zone, 2022)
The purpose of the very article was to conduct a thorough analysis of the lexical vocabulary that is target onto the women and differentiate the vocabulary used for the males. The notion of gender bias in the language has been the issue to be solved for a long period of time. This article aims at identifying. the gender bias along with the clear example and the place of usage, moreover to find the ways to make a language free of gender bias. Along with determining the bias of gender, the focus comes onto the linguistic mistreatment that women receive. Although both females and males happen to have gender bias in the language, it turned out that the language has created a fruitful vocabulary towards men, whilst women have less words associate with them or used to describe them. That is the result of the occurrence of the concept of ‘feminine forms’. Feminine forms were introduced into English speech in order to get away from the attachment of the profession to a particular gender, thus avoiding prejudices regarding gender distributions and responsibilities in society. The results of the study are as follow, introducing appropriate gender-neutral terms and feminine forms in the language.